1993
DOI: 10.1213/00000539-199301000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Thiopental Induction Dose Requirements

Abstract: Dose requirements for thiopental anesthetic induction have significant age- and gender-related variability. We studied the association of the patient characteristics age, gender, weight, lean body mass, and cardiac output with thiopental requirements. Doses of thiopental, infused at 150 mg/min, required to reach both a clinical end-point and an electroencephalographic (EEG) end-point were determined in 30 males and 30 females, aged 18-83 yr. Univariate least squares linear regression analysis revealed outliers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…This observation is supported by the fact that the dosages of the potentially dangerous drugs, fentanyl and thiopental, were matched to age-related changes in redistribution kinetics and drug metabolism (4.2±1.4 µg/kg and 2.0±0.1 mg/kg, respectively) [3]. Furthermore, since the skill of the surgeon significantly alters patient outcome [4,5], the results of this study may have been positively influenced by the fact that all operations were performed by the same surgeon.…”
Section: Discussionmentioning
confidence: 79%
“…This observation is supported by the fact that the dosages of the potentially dangerous drugs, fentanyl and thiopental, were matched to age-related changes in redistribution kinetics and drug metabolism (4.2±1.4 µg/kg and 2.0±0.1 mg/kg, respectively) [3]. Furthermore, since the skill of the surgeon significantly alters patient outcome [4,5], the results of this study may have been positively influenced by the fact that all operations were performed by the same surgeon.…”
Section: Discussionmentioning
confidence: 79%
“…A traditional pharmacokinetic compartment model does not include cardiac output as a variable for calculating or predicting drug concentration (10,11,21,22). Avram et al (24) reported that the induction dose of thiopental was independent of cardiac output when using an electroencephalogram end point. Cardiac output is a determinant of the volumes of central and peripheral compartments (23).…”
Section: Discussionmentioning
confidence: 99%
“…Specific electroencephalographic changes might also be used to define a future end‐point for a chosen depth of anaesthesia (Hudson et al. 1983; Avram et al. 1993).…”
Section: Discussionmentioning
confidence: 99%